Firing transformations of an argentinean calcareous commercial clay - Serra, Maria Florencia (2013)
Mineralogical transformations caused by firing are usually studied by XRD methods only semi-quantitatively. In this work the original mineral disappearance and the neo-mineralization were evaluated quantitatively. Furthermore an indirect non crystalline phase quantification was performed under 1100 ºC was also carried out using the quartz content as internal standard. This study specifically discusses the behavior of an Argentinean white calcareous earthenware commercial when subjected to traditional ceramic firing, besides the technological importance of this particular material, it acts as a model for other clay based ceramic materials. Materials were subjected to thermal treatments between 700 ºC and 1100 ºC. A preliminary sintering characterization was carried out by contraction and porosity evolution. Simultaneous thermogravimetric and differential thermal analysis (TG-DTA) was carried out to elucidate the actual temperature at which the chemical changes occur. Finally, a quantitative analysis based on the Rietveld refinement of the X-ray diffraction patterns was performed to characterize the crystalline phases present in both the clay and in the materials obtained after different thermal treatments. The actual chemical reactions are proposed. The phases identified after firing at traditional working temperature (1040 ºC) are quartz, plagioclase, and the Spinel type alumino-silicate, accompanied by the non-diffracting un-reacted metakaolin and some amount of amorphous glassy phase. At intermediate temperatures (900 ºC) the presence of gehlenite was also detected. The carbonates (calcite and dolomite) presence and decomposition were also evaluated and demonstrated to determine the sintering characteristics of this material.